Estimativa da Et Diária Utilizando os Algoritmos Sebal e S-Sebi - dos Santos, Carlos Antonio Costa; da Silva, Bernardo B.; Rao, Tantravahi V. Ramana (Ciência e Natura, 2007)
The objective this paper is analyze the performance the algorithmsSEBAL and S-SEBI in the estimating of the daily evapotranspiration (ET),using techniques of remote sensing and Landsat 5-TM images. To principalit differentiates among the algorithms comes in the fact of S-SEBI not toneed of information of the surface to estimate the components of the energybalance. The applications of the SEBAL and S-SEBI algorithms aresatisfactory for the obtaining of ET. S-SEBI presents results similar to theSEBAL, evidencing to be a promising tool in the obtaining of ET for areasthat dont have a weather station.